Pierre Macherey and the case of literary production - Montag, Warren; Wasser, Audrey (Northwestern University Press, 2022)
"This collection revisits A Theory of Literary Production (1966) to show how Pierre Macherey's remarkable--and still provocative--early work can contribute to contemporary discussions about the act of reading and the politics of formal analysis. Across a series of historically and philosophically contextualized readings, the volume's contributors interrogate Macherey's work on a range of pressing issues, including the development of a theory of reading and criticism, the relationship between the spoken and the unspoken, the labor of poetic determination and of literature's resistance to ideological context, the literary relevance of a Spinozist materialism, the process of racial subjectification and the ontology of Blackness, and a theorization of the textual surface."--